2008
DOI: 10.1186/cc6147
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia and sedation in the intensive care unit: an overview of the issues

Abstract: Analgesic and sedative medications are widely used in intensive care units to achieve patient comfort and tolerance of the intensive care unit environment, and to eliminate pain, anxiety, delirium and other forms of distress. Surveys and prospective cohort studies have revealed wide variability in medication selection, monitoring using sedation scales, and implementation of structured treatment algorithms among practitioners in different countries and regions of the world. Successful management of analgesia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 50 publications
0
25
0
2
Order By: Relevance
“…Pain is one of the main causes of distress in intensive care units (ICU) patients [1]. Studies in ICU have revealed that pain, agitation, and anxiety may evoke a stress response leading to adverse effects such as increased myocardial oxygen consumption, hypercoagulability, immunosuppression, dysynchronous mechanical ventilation, and inadvertent removal of endotracheal tubes and other monitoring devices [2–4].…”
Section: Introductionmentioning
confidence: 99%
“…Pain is one of the main causes of distress in intensive care units (ICU) patients [1]. Studies in ICU have revealed that pain, agitation, and anxiety may evoke a stress response leading to adverse effects such as increased myocardial oxygen consumption, hypercoagulability, immunosuppression, dysynchronous mechanical ventilation, and inadvertent removal of endotracheal tubes and other monitoring devices [2–4].…”
Section: Introductionmentioning
confidence: 99%
“…26 Nursing response to patient agitation, especially in the mechanically ventilated critically ill patient, often includes increasing the level of sedation. However, over-sedation has been shown to significantly increase the duration of mechanical ventilation and the risk of concomitant complications, as well as ICU length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…These include reducing anxiety, treating pain or delirium, facilitating sleep, preventing harm to self or caregivers, controlling vital signs, preventing consciousness during use of muscle relaxants, and facilitating mechanical ventilation. 1 As a result, existing evidence regarding best ICU sedation practices spans a wide variety of patients, indications, approaches, and end points. Because much of the literature specific to critical care sedation focuses on the mechanically ventilated patient, this chapter specifically addresses the use of sedation and analgesia in intubated patients undergoing mechanical ventilation in an ICU setting.…”
Section: Critically Ill Patients?mentioning
confidence: 99%